Granger causality of the local Hadley cell and large-scale cloud cover over South Africa - Dawn D. Mahlobo; Thando Ndarana; Stefan W. Grab; Francois Engelbrecht (South African Journal of Science, 2019)
This study demonstrates that Hadley cell dynamics could be used as a proxy to determine cloud cover and thus solar energy potential over South Africa. Granger causality was used to investigate causal interactions between the Hadley cell and cloud cover for the period 1980–2015, and such links were established. Areas of strong causality are found over the northwestern parts of South Africa. Moreover, weak causality from cloud cover to the Hadley cell does exist, with vertical velocity being the main variable responsible for this causality, which hence indirectly links cloud cover to Hadley cell causality.